Loanwords as Cultural Representation: Indonesian Lexicon of “Durian” in Mandarin Chinese - Kumala Dewi Wundari; Fransiska Wiratikusuma (International Journal Labs, 2026)
The relationship between Indonesia and China left tangible imprints on the Mandarin lexicon. One such trace can be found in the loanword ?? (liúlián), which refers to durian. This article examines the loanword as a product of non-colonial language contact and as a reflection of how cultural experiences from Southeast Asia—particularly Indonesia—have been introduced into and utilised within Mandarin Chinese. The study approaches loanwords not merely as matters of linguistic form, but as part of a broader process of cultural meaning-making. This research adopts a qualitative approach that integrates historical analysis, structural linguistic analysis, and perspectives from cultural linguistics. The data are drawn from authoritative Mandarin dictionaries, modern Mandarin texts, and historical sources discussing maritime trade and the mobility of Chinese communities in Southeast Asia in earlier periods. Through this approach, the analysis focuses on the origin of the term, the ways in which Mandarin adapts foreign sounds and characters, and the cultural meanings associated with the use of ?? (liúlián) in Mandarin. The findings indicate that the incorporation of ?? (liúlián) into Mandarin was not driven solely by the need to name a foreign object, but was closely tied to direct experience through trade and socio-cultural interaction. In Mandarin, ?? (liúlián) does not merely denote a tropical fruit known for its distinctive aroma; rather, it serves as a living record of historical connections and cross-cultural exchange, as well as a symbol of longstanding ties and mutual engagement between Southeast Asian societies and China.